ASPEK HUKUM TENTANG PERJANJIAN YANG DI BUAT DI BAWAH PAKSAAN (DWANG) MENURUT BURGERLIJK WETBOEK (BW) (Studi Putusan Nomor 759 K/Pdt/ 2017) - Kurniawati, Wa Ode Intan; Yusuf, Niken Yulian (Jurnal Multidisipliner Bharasumba, 2023)
The purpose of this research is to determine whether the legal considerations of the judges of the Supreme Court of the Republic of Indonesia in deciding case No. 759K/Pdt/2017 are in accordance with the applicable norms and regulations. The type of research used in this study is normative research, which is descriptive analysis. The data sources were obtained by collecting primary and secondary data. The primary data were obtained from the Civil Code. Meanwhile, the secondary data were obtained through literature books, legislation, official documents, and websites. The data collection method involved inventorying these data, which were then presented in a systematic description. Based on the research findings and discussions that serve as legal considerations for the judges of the Supreme Court of the Republic of Indonesia in deciding case No. 759K/Pdt/2017, it is determined that the proof of coercion elements in an agreement must demonstrate whether both parties entering into the agreement were in a balanced position and whether one of the parties had acted in bad faith in making the agreement, as stated in Article 1338 paragraph (3) and Article 1339 of the Civil Code, which stipulate that agreements must be executed in good faith and fairness. Furthermore, coercion elements occurring in an agreement are considered contradictory to Article 1320 of the Civil Code, which regulates the requirements for the validity of an agreement. The legal consequence for a sales agreement containing coercion elements is that it can be nullified by one party. The nullification occurs when one of the subjective conditions is not fulfilled. In such cases, the agreement is not null and void by operation of law, but one of the parties can request its nullification. The agreement remains binding on both parties unless it is canceled (by a judge) upon the request of the party entitled to request the nullification (an incapable party or a party who entered into the agreement involuntarily). In this situation, the defendant is obligated to return the land certificate that has been sold and compensate for the damages by paying the entire litigation costs.